Ketamine Infusion Associated with Improved Neurology in a Patient with NMDA Receptor Encephalitis. (19th August 2013) - MacMahon, Michael; Naysmith, Morag R.; McCallion, Stephanie; Rhodes, Jonathan
Abstract : A young lady was ventilated on intensive care for a prolonged period with NMDA receptor encephalitis. She had undergone steroid, immunoglobulin, and plasmapheresis with no evidence of recovery. Her main management issue was the control of severe orofacial and limb dyskinesia. Large doses of sedating agents had been used to control the dystonia but were ineffective, unless she was fully anaesthetised. The introduction of a ketamine infusion was associated with a dramatic improvement in her symptoms such that it was possible to remove her tracheostomy two days after commencement. She was discharged shortly after that and is making a good recovery. The successful use of ketamine has not previously been described in this context, and we hope this case report will provide some insight into the management of this rare but serious condition.